2021
DOI: 10.1590/1679-78256330
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Foamed Concrete Beam under Flexural Using Traction-Separation Relationship

Abstract: The aim of the current project is to carry out the FEA framework for predicting the flexural strength of notched foam concrete tested under three-point bending following the conducted experimental set-up. The investigated testing series have a variation of notch size opening in the foamed concrete beam. The Tractionseparation relationship was used as a constitutive model to incorporate independent material properties and used in the modelling framework. Modelling techniques of 2D XFEM and CZM were adopted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…[n]{u} − {u} p n = {0} na Ss + Sp (29) where the matrix [C] is the material's compliance matrix [18]:…”
Section: Kinematic Boundary Conditionsmentioning
confidence: 99%
“…[n]{u} − {u} p n = {0} na Ss + Sp (29) where the matrix [C] is the material's compliance matrix [18]:…”
Section: Kinematic Boundary Conditionsmentioning
confidence: 99%
“…The result showed that the VCCT is more sensitive compared to the XFEM and CZM. Meanwhile, Omar et al [29] worked on foam concrete beams using the XFEM and CZM and found that there was less agreement within the CZM due to the simplification of adopting a failure path. However, the LEFM theory adopted within the ABAQUS software is only applicable for materials that have a relatively small plastic process zone [30].…”
Section: Introductionmentioning
confidence: 99%
“…Various modelling techniques can be incorporated with TSL, such as the extended finite element method (XFEM), virtual crack closure technique (VCCT) and cohesive zone model (CZM). A study by H. Ahmad et al, (2021) and Structures, 2022, 19(6), e460 3/12 bending foam concrete beam using XFEM and CZM method and found that XFEM performed better than the CZM in predicting the load capacity. While Yu et al, (2021) simulating beam nuclear graphite by using the XFEM, the CZM and the VCCT methods.…”
Section: Introductionmentioning
confidence: 99%